Young and restless : the girls who sparked America's revolutions - Kahn, Mattie (Viking, 2023)
"The untold history of the people who helped spark America's most important social movements from the Revolutionary War to today: teenage girls. Nine months before Rosa Parks, 15-year-old Claudette Colvin was arrested for refusing to give up her seat on a segregated bus in Montgomery, Alabama. In 1912, women's rights activists organized a massive march in support of women's suffrage, led up Fifth Ave in Manhattan, not by Susan B. Anthony, but by a teenage Chinese immigrant named Mabel Ping-Hua Lee. Half a century before the better known movements for workers' rights began, over 1,500 girls--some as young as ten--walked out of factories in Lowell, Massachusetts, demanding safer working conditions and higher wages in one of the nation's first-ever labor strikes. Young women have been disenfranchised and discounted, but the true history of major social movements in America reveals their might: they have kicked off almost every single one. Young and Restless tells the story of one of the most foundational and underappreciated forces in moments of American revolution: teenage girls. From the American Revolution itself to the civil rights movement to nuclear disarmament protests and the women's liberation movement, through Black Lives Matter and school strikes for climate, Mattie Kahn uncovers how teen girls have leveraged their unique strengths, from fandom to intimate friendships, to organize and lay serious political groundwork for movements that often sidelined them. Their stories illuminate how much we owe to teen girls throughout the generations, what skills young women use to mobilize and find their voices, and, crucially, what we can all stand to learn from them"--